Vertical vibration isolator having piecewise-constant restoring force. - Araki, Yoshikazu (Earthquake engineering & structural dynamics.)
We present a vertical vibration isolator having a piecewise-constant restoring force, which belongs to a class of passive and nonlinear vibration isolators. In vertical vibration isolation, direct use of low-stiffness elements leads to unacceptably large deformations due to self-weight. To overcome the difficulty, we apply a combination of constant-force springs, each of which sustains a constant load regardless of its stretch. By arranging the constant-force springs, so that the isolator has a piecewise-constant restoring force, we alleviate the problem of the excessive deformation caused by self-weight, provide stability at the static equilibrium state along with the self-centering capability, and realize a large stroke while keeping the mechanism simple and compact. Further, we attempt to limit the response acceleration within a tolerance regardless of the frequency spectrum and the magnitude of earthquake ground motions. We demonstrate the effectiveness of the present isolator through shaking table tests and numerical simulations.